Comparing Kinetics of Xylem Ion Loading and Its Regulation in Halophytes and Glycophytes. (6th November 2019) - Zarei, Mahvash; Shabala, Sergey; Zeng, Fanrong; Chen, Xiaohui; Zhang, Shuo; Azizi, Majid; Rahemi, Majid; Davarpanah, Sohrab; Yu, Min; Shabala, Lana
Abstract: Although control of xylem ion loading is essential to confer salinity stress tolerance, specific details behind this process remain elusive. In this work, we compared the kinetics of xylem Na + and K + loading between two halophytes ( Atriplex lentiformis and quinoa) and two glycophyte (pea and beans) species, to understand the mechanistic basis of the above process. Halophyte plants had high initial amounts of Na + in the leaf, even when grown in the absence of the salt stress. This was matched by 7-fold higher xylem sap Na + concentration compared with glycophyte plants. Upon salinity exposure, the xylem sap Na + concentration increased rapidly but transiently in halophytes, while in glycophytes this increase was much delayed. Electrophysiological experiments using the microelectrode ion flux measuring technique showed that glycophyte plants tend to re-absorb Na + back into the stele, thus reducing xylem Na + load at the early stages of salinity exposure. The halophyte plants, however, were capable to release Na + even in the presence of high Na + concentrations in the xylem. The presence of hydrogen peroxide (H2 O2 ) [mimicking NaCl stress-induced reactive oxygen species (ROS) accumulation in the root] caused a massive Na + and Ca 2+ uptake into the root stele, while triggering a substantial K + efflux from the cytosol into apoplast in glycophyte but not halophytes species. The peak in H2 O2 production was achieved faster in halophytes (30 min vs 4 h) and was attributed to the increased transcript levels of RbohE . Pharmacological data suggested that non-selective cation channels are unlikely to play a major role in ROS-mediated xylem Na + loading.